Optimalisasi Play Outdoor dalam Menstimulasi Motorik Anak pada Taman Kanak-Kanak Pelangi Bulukumba - Usman Usman; Sutra Awaliyah Darfin; Nidha Eka Restuti Munawir; Ruslan Mattoreang; Tawakkal Tawakkal (Lembaga Pengembangan Kinerja Dosen, 2025)
This activity aims to improve the motor skills of early childhood through outdoor play activities at Pelangi Bulukumba Kindergarten. The activity was conducted over six sessions in May 2025 by lecturers and students of the Early Childhood Education Study Programme at STAI Al Gazali Bulukumba. The activity stages began with coordination with the school, observation, development of a lesson plan, instrument validation, and the implementation of a pre-test, outdoor play interventions, and a post-test. The activities included various gross and fine motor games, such as zig-zag running, jumping, and moving small objects. Evaluation results showed a significant improvement in children's motor skills, with 100% of children achieving the “Very Good Development” category after the activity. A paired sample t-test showed a significant difference (p = 0.000), indicating the effectiveness of this method. These findings reinforce motor development and developmental ecology theories, which emphasise the importance of the natural environment in supporting children's growth and development. In conclusion, outdoor play is effective in improving children's motor skills and is recommended for regular integration into the kindergarten curriculum. Parent involvement and the development of modules, along with ongoing evaluation, are necessary for the sustainability of this programme.Keywords: gross motor skills, fine motor skills, outdoor play, locomotor skills,